Sociobiology Approach in Educational Sociology and Animal Ecology Courses: Learn Social Behavior and Character Building from the Nature - Dhanu Pitoyo; Berkat Berkat (FKIP, Universitas Palangka Raya, 2023)
Sociobiology is a science that studies the biological basis of social behavior of animals and humans. The field of sociobiology is closely related to moral education which is important and crucial in the learning process at all levels of education. This research is aimed: (1) to implement the sociobiology approach in educational sociology and animal ecology courses; and (2) to describe the social behavior values that acquired by the students after participating in learning with a sociobiology approach. This research is a descriptive qualitative research. The participants involved in this study consisted of 30 undergraduate students from the Department of Sociology and 25 undergraduate students from the Biology Education Study Program of University of Palangka Raya. Data were collected using questionnaires which were distributed to participants/students during lectures. The social behavior values that acquired by the students are beyond expectations. They are able to have a social perspective on the given animal behavior videos. The values of social behavior obtained by students include: sharing happiness; taking care of each other; tolerance; adaptation; team work; solidarity; friendship; independence; and leadership.